Synthesis of new 3-arylindole-2-carboxylates using beta,beta-diaryldehydroamino acids as building blocks. Fluorescence studies - Queiroz, Maria João R. P. (2007)
Several new methyl 3-arylindole-2-carboxylates were synthesized in high yields using a metal-assisted [Pd(OAc)2/Cu(OAc)2, DMF, 130 oC] intramolecular C-N cyclization of beta,beta-diaryldehydroamino acids, developed by us, thus extending the scope of this reaction. The latter were obtained by a bis-Suzuki coupling of a beta,beta-dibromodehydroalanine with arylboronic acids bearing either electron-donating groups (EDGs) or electron-withdrawing groups (EWGs). We were able to establish general conditions for this coupling reaction [PdCl2dppf.CH2Cl2 1:1(20 mol%), boronic acid (5 equiv.), Cs2CO3 (1.4 equiv.), THF/H2O 1:1, 80 oC]. This strategy constitutes a novel, general and unprecedent approach to the synthesis of 3-arylindole-2-carboxylates. The fluorescence of the differently substituted indoles prepared was studied in several polar and non-polar solvents. In general the new indoles exhibit a solvent sensitive emission. The indoles with EDGs (OCH3 and SCH3) have reasonable fluorescence quantum yields in all solvents except in water. The indole with the cyano groups shows high fluorescent quantum yields in all solvents studied, despite the lower solvent sensitivity of its emission. The indole with the acetyl groups only exhibits reasonable fluorescence quantum yields in protic solvents. The fluorescence studies show that the new 3-arylindole-2-carboxylates are good candidates to be used as fluorescent probes.